(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A government organization has predetermined goals. Success in achieving these goals does not only depend on government operational funds, facilities and infrastructure and technology, but also depends on human resources. Therefore, this research aims to examine the influence of work motivation and employee abilities on the effectiveness of local government organizations, with the hypothesis "there is a positive influence of work motivation and employee abilities on organizational effectiveness". The research method used is a causal survey method with multiple regression analysis techniques. This research is quantitative research so that the data obtained, processed and analyzed statistically (parametrically). Based on the data analysis that has been carried out, this research produces findings which are concluded as follows: (i) work motivation and ability together have a significant effect on organizational effectiveness; (ii) work motivation alone (partially) has a significant effect on organizational effectiveness; (iii) ability alone (partially) has a significant effect on organizational effectiveness.